Recognition of transient instability scenarios of the receiving-end grid and control strategy optimization - WANG Bowen; WANG Longfei; DONG Wei; ZHUO Guying; HUA Wen; SHENTU Leixuan (Zhejiang dianli, 2023)
Under the influences of AC-DC coupling， uncoordinated network-source development， and new energies that fail to meet the demand of grid-related performance， power system stability is becoming a point of extreme gravity. The correlation characteristics of transient voltage and power angle stability of the receiving-end grid are analyzed. Two transient instability modes with transient voltage and transient power angle instability as the dominant causal factors and their specific evolution processes are discussed based on the transient stability mechanism. Afterward， the effects of the optimal control measures on grid layout， power structure， network-source coordination， power distribution， and source-load interaction on optimizing the transient stability are reviewed and verified， and the traditional stability control measure of limiting unit output is not adopted. The study of the evolution of transient instability patterns and simulation analysis provides a reliable reference for identifying transient instability scenarios of key units in the receiving-end grid and formulating control measures.